OPTIMIZATION OF ACHIEVEMENTS ASSESSMENT OF PRESCHOOL CHILDREN - Ramanauskienė, Sada; Norviliene, Aida (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2017)
In this article the authors present the system assessing the achievements of preschool children in Lithuania, the teacher's opinion regarding the description of achievements assessment of preschool children and its adaptation in a preschool education institution. This article presents the recommendations for the optimization of achievements assessment of preschool children. The quantitative research was applied in accordance with the interpretative attitude, a total of 130 preschool education teachers and managers from Klaipeda region. The results: optimization of implementation of description, assessing the achievements of preschool children, by preparing the model of description; motivation of teachers to improve the skills of assessing the achievements of children, rationalizing and allocating the cost of labor in the teaching process; better education planning process with regard to children's individual needs and abilities, which are determined in the model of achievements assessment of preschool children.